Estudo fitoquímico e potencial bioativo de Amburana acreana Ducke A.C.Sm. - Ferreira, Adrianne Bastos (2024)
Plant species of the Amburana genus are used in folk medicine to treat diseases of the respiratory system. However, scientific studies highlighting the therapeutic potential of these species are still incipient. In this sense, this study aimed to study the phytochemical profile of the leaf extract of Amburana acreana and evaluate the bioactive potential of this species. The collection of leaves and preparation of the hydroethanolic extract (EAA) were carried out on the campus of the Federal University of Rondônia (UNIR), in the city of Ji-Paraná. In the leaf extract of A. acreana, it was possible to identify the following compounds by HPLC – DAD: protocatechuic acid (1), phydroxybenzoic acid (2), vanillic acid (3), p-coumaric acid (4), syringic acid (5), 4-β-Dglucopyranosyloxybenzyl ester (7), coumarin (8), amburoside B (9) and glycosylated flavonol derivatives (6, 10 and 11). Compounds 2, 3, 7, 8, 9 and glycosylated campesterol were isolated by classical column chromatography and identified by Nuclear Magnetic Resonance spectroscopy (1D and 2D). The antioxidant and anti-inflammatory potential of EAA and amburoside B (AMBB) were evaluated by in vitro assays by determining the nitric oxide concentration and 5-lipoxygenase enzyme activity. EAA showed IC50 = 347.2 μg mL-1 and IC50 = 151.1 μg mL-1 for reducing NO levels and reducing 5-LOX enzymatic activity, respectively. AMBB reduced NO levels at the concentrations tested (6.2 to 200.0 μM). However, the compound showed a reduction in 5-LOX enzymatic activity only at a concentration of 100.0 μM, the highest concentration tested. EAA and AMBB were also evaluated for toxicity using the MTT assay, and both did not show mitochondrial alterations in SH-SY5Y cells. In addition, an in vitro screening using the thermal shift assay and in silico molecular dynamics assays with AMBB was performed to evaluate the antileishmanial capacity of the compound. The results demonstrated that AMBB has antiparasitic activity and may be a promising compound in the development of new drugs against leishmaniasis.